2016
DOI: 10.1371/journal.pone.0154825
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis in Pregnancy: A Systematic Review

Abstract: BackgroundIn countries with low tuberculosis (TB) incidence, immigrants from higher incidence countries represent the major pool of individuals with latent TB infection (LTBI). The antenatal period represents an opportunity for immigrant women to access the medical system, and hence for potential screening and treatment of LTBI. However, such screening and treatment during pregnancy remains controversial.ObjectivesIn order to further understand the prevalence, natural history, screening and management of LTBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 29 publications
0
53
0
7
Order By: Relevance
“…Maternal health controls represent an excellent opportunity to screen women belonging to risk groups for TB in order to initiate early diagnosis and treatment of active TB, or preventive therapy when indicated, as has been recommended in scientific publications 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Maternal health controls represent an excellent opportunity to screen women belonging to risk groups for TB in order to initiate early diagnosis and treatment of active TB, or preventive therapy when indicated, as has been recommended in scientific publications 26,27…”
Section: Discussionmentioning
confidence: 99%
“…[1214] In settings with lower risk of TB transmission, a positive TST may reflect false positivity due to BCG vaccination rather than Mtb infection, leading to a higher proportion of TST+/IGRA−. [15] Additionally, most studies have been cross-sectional, and do not capture potential dynamic effects of peripartum stage on LTBI diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Both trials reported high rates of mortality and hospitalization in all arms 18,31. Reporting of drug safety in pregnancy was extremely limited for all regimens despite this issue being of considerable clinical interest both because patients may become pregnant while on therapy and because LTBI treatment may be warranted in select groups of pregnant patients at high risk of progression 89. A recent systematic review on LTBI treatment in pregnancy also found little data regarding adverse events 89.…”
mentioning
confidence: 99%